Optimizing Information Technology Investment Using the Total Cost of Ownership (TCO) Approach: A Case Study of a Property Company - Tania Ayu Sekar Arum; Lukman Abdurrahman (Eduvest - Journal of Universal Studies, 2026)
Information technology (IT) investment has become an essential component for improving operational efficiency, service quality, and business competitiveness in the property industry. However, many companies still focus only on initial acquisition costs without considering the overall expenses incurred throughout the lifecycle of IT assets. This study aims to evaluate and optimize IT investment at Ray White CBD Bandung using the Total Cost of Ownership (TCO) approach. The research employed a quantitative descriptive method using primary and secondary data collected through interviews, observation, and document analysis. The TCO approach was used to identify and calculate all IT-related costs, including acquisition, maintenance, support, and training costs during the 2022–2024 period. The findings reveal that software costs represented the largest component of IT investment, followed by equipment maintenance, printer assets, and employee training. The study also identified several hidden costs, such as downtime, vendor dependency, and troubleshooting time, which significantly influenced operational efficiency and financial performance. The implementation of the TCO approach helped the company understand the real cost structure of IT ownership and improve budget planning. In conclusion, the TCO approach provides a comprehensive framework for making strategic, sustainable, and cost-effective IT investment decisions in property companies.